2017
DOI: 10.1001/jamainternmed.2017.3947
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care for Opioid and Alcohol Use Disorders in Primary Care

Abstract: IMPORTANCE Primary care offers an important and underutilized setting to deliver treatment for opioid and/or alcohol use disorders (OAUD). Collaborative care (CC) is effective but has not been tested for OAUD.OBJECTIVE To determine whether CC for OAUD improves delivery of evidence-based treatments for OAUD and increases self-reported abstinence compared with usual primary care. DESIGN, SETTING, AND PARTICIPANTSA randomized clinical trial of 377 primary care patients with OAUD was conducted in 2 clinics in a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(165 citation statements)
references
References 60 publications
3
161
0
Order By: Relevance
“…Collaborative care for OAUD was a system-level clinical intervention that used care coordinators and a patient registry to support the delivery of medication-assisted treatment and/or a six-session motivational interviewing- and cognitive therapy- based brief treatment (Ober et al, 2015; Rollnick & Miller, 1991; Watkins et al, In press; Watkins et al, 2017). In the current study, implementation refers to the process of integrating the continuum of care for OAUD using collaborative care into the two primary care clinics, including screening, brief intervention, MAT, and brief therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative care for OAUD was a system-level clinical intervention that used care coordinators and a patient registry to support the delivery of medication-assisted treatment and/or a six-session motivational interviewing- and cognitive therapy- based brief treatment (Ober et al, 2015; Rollnick & Miller, 1991; Watkins et al, In press; Watkins et al, 2017). In the current study, implementation refers to the process of integrating the continuum of care for OAUD using collaborative care into the two primary care clinics, including screening, brief intervention, MAT, and brief therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Effective integration of OAUD treatment into primary care settings could increase access to treatment for many individuals with OAUDs. However, in order for OAUD treatment to be adopted and integrated within existing practices, organizations must have the capacity to deliver the treatment (Meyer, Davis, & Mays, 2012; Ober et al, 2015; Watkins et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…not specific to OUD). These studies found higher rates of initiation and engagement when patients were identified in specialty settings or receiving care in specialty settings (Harris & Bowe, 2008; Harris, Bowe, Finney, & Humphreys, 2009) although primary care (Kim, Saitz, Cheng, et al, 2011) and collaborative care initiatives have also shown to be successful (Watkins, Ober, Lamp, et al, 2017) at engaging patients. Other studies found that patients with greater criminal justice involvement, addiction severity, and racial/ethnic minorities often had relatively lower probabilities of treatment initiation and engagement (Acevedo, Garnick, Dunigan, et al, 2015; Brown, Bennett, Li, & Bellack, 2011; Lee, Garnick, O’Brien, et al, 2012) but this was not always observed (Bensley, Harris, Gupta, et al, 2017), reflecting variation in patient populations across settings.…”
Section: Resultsmentioning
confidence: 99%
“…Although some patients may receive high quality care for other SUDs that does not involve MAT, the evidence does not currently support this as a first line approach for OUD. Additionally, studies such as Watkins, Paddock, Hudson, et al, 2017 have demonstrated the limitations of general SUD measure reliability for OUD and pitfalls of their misapplication to OUD, limiting clinical validity. For example, in many systems, the initiation of MAT may reflect underlying addiction severity requiring risk adjustment as a confounder for outcomes such as mortality in addition to serving as a process measure approximating quality care.…”
Section: Discussionmentioning
confidence: 99%
“…We further describe these below and in Ober et al (2015). During this phase, we developed a collaborative care service delivery protocol in response to identified barriers to delivering OAUD treatment in the FQHC Watkins et al, 2017).…”
Section: Acknowledgmentsmentioning
confidence: 99%